Análisis energético del esquema tecnológico del proceso de pirólisis rápida para la producción de bioaceites a partir de neumáticos de desecho (2019)
In this project, initially a review of the physico-chemical characterization of waste tires is carried out, taking into account both elemental and proximate analysis to determine the distribution of products in the fast pyrolysis, as the calorific power to assess the energy potential of the biomass implemented. Subsequently, the technological scheme of the rapid pyrolysis process and the operational conditions of each of the stages that comprise it are defined, considering in the first instance a pre-treatment stage, which includes grinding, sifting, cleaning and drying the tire to increase the performance and quality of bio-oil. The second stage corresponds to rapid pyrolysis, in which the thermal decomposition of the biomass occurs in a solid product (carbonized) and a gaseous (volatile material) in the absence of oxygen, for which it is necessary to know the kinetics of the process. Then, the volatile material obtained is passed through a condensation stage, in which two heat exchangers are used to obtain the water-free bio-oil; finally, because the product contains oxygenated compounds that are contaminants in the biofuel, an adaptation stage is required in order to obtain a purified bio-oil of good quality and high calorific value that can be used as transport fuel, so that the hydrotreatment process is studied for this last stage.